ANALYSIS OF PROFITABILITY, SOLVABILITY, TOTAL ASSET TURNOVER AND COMPANY SIZE ON GOING CONCERN AUDIT OPINION - F.Agung Himawan D; Albertus Karjono; Rahel Ratuminar Tiarasari (RADJA PUBLIKA, 2025)
This study aims to determine the effect of profitability, solvency, total assets turnover and company size on going concern audit opinion in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study uses a purposive random sampling method which will be used to determine the number of samples, the sample in this study is 100 companies, this company data is secondary data obtained from the company's annual financial reports for the 2017-2021 period with a total sample of 500 company financial reports. The data analysis technique used in this study uses logistic regression analysis. The results of this study indicate that (1) ROA has a significant negative effect on going concern audit opinion, (2) DAR has a significant positive effect on going concern audit opinion, (3) TATO has a significant negative effect on going concern audit opinion, (4) SIZE has a significant negative effect on going concern audit opinion.